Brain-derived neurotrophic factor and inflammation in depression: Pathogenic partners in crime? - Porter, Grace A; O’Connor, Jason C (World journal of psychiatry, 2022)
Major depressive disorder is a debilitating disorder affecting millions of people each year. Brain-derived neurotrophic factor (BDNF) and inflammation are two prominent biologic risk factors in the pathogenesis of depression that have received considerable attention. Many clinical and animal studies have highlighted associations between low levels of BDNF or high levels of inflammatory markers and the development of behavioral symptoms of depression. However, less is known about potential interaction between BDNF and inflammation, particularly within the central nervous system. Emerging evidence suggests that there is bidirectional regulation between these factors with important implications for the development of depressive symptoms and anti-depressant response. Elevated levels of inflammatory mediators have been shown to reduce expression of BDNF, and BDNF may play an important negative regulatory role on inflammation within the brain. Understanding this interaction more fully within the context of neuropsychiatric disease is important for both developing a fuller understanding of biological pathogenesis of depression and for identifying novel therapeutic opportunities. Here we review these two prominent risk factors for depression with a particular focus on pathogenic implications of their interaction.